Clients' Perspectives on Outcomes and Mechanisms of Bereavement Counselling: A Qualitative Study. (October 2017) - Klasen, Mary; Bhar, Sunil S.; Ugalde, Anna; Hall, Christopher
Abstract : Objectives: Bereavement counselling (BC) seeks to address pervasive grief and facilitate healthy adaptation to loss. There is limited understanding of BC outcomes and the mechanisms that facilitate outcomes. Quantitative measures tend to focus on clinical rather than salutogenic outcomes such as post‐traumatic growth. Furthermore, there is limited research about the contribution that client and counsellor attributes and the therapeutic alliance make to effective outcomes. This study addressed two questions: What are the outcomes of BC for clients? What are the mechanisms of BC that generate these outcomes? Method: Participants were 16 former clients of an Australian specialist BC centre. A semi‐structured interview was conducted to generate information about clients' BC experience. Responses were subjected to thematic analysis. Results: Three themes were induced from the data. First, Seeking Bereavement Counselling: I was desperate. I knew I needed help, comprised recognition of need and help seeking behaviour. Second, Working Collaboratively: Let's work together to see what we can achieve, incorporated client and counsellor attributes, collaborative therapeutic relationship, and client centred interventions. Third, Appraising Efficacy: I'm learning to live again, included reduction in grief symptomatology, adaptation to loss, and positive growth. Conclusion: Participants offered detailed information about their experience of BC. The study highlighted three important mechanisms of BC that enable positive outcomes for participants: client agency, client‐counsellor collaboration, and person centred interventions. The study supports BC as a relational context where the salient needs of bereaved people are respected and addressed, enabling change to occur.